KREDIBILITAS TEKS HOAX DI MEDIA SIBER - A. Yudo Triartanto (Jurnal Komunikasi, 2015)
Text hoax containing more massive lies and hatred manifested in the form of news, data, images, and photos. Hoax inherent in the cyber media becomes a necessity, when narrated in social media. Users of social media becomes difficult to select and sort, where the news is factual where news is a lie. All became faint. Society has finally been accustomed to receiving everything hoax. Even the news that contains hatred. The government, through the police, and then perform preventive efforts against hoax, so as not to spread hoax then become a culture and ideology increasingly steady.